Assessment of Knowledge, Attitude and Practice based Survey on the Use of Ultrasonics in Endodontics among General Practitioners and Endodontists of Nepal - Ghimire, Siddharth; Dhital, Shweta; Roy, Deepak Kumar; Poudel, Priyanka; Roy, Roshan Kumar (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Introduction: Endodontic practice has seen a massive technological leap over the past few decades which have improved the prognosis of the treatment performed. Ultrasonics simplifies complex endodontic procedures like navigating calcified canals and removing obstructions. Ultrasonic endodontic treatment, for both primary and permanent teeth, streamlines procedures, minimizing appointments, patient stress, and expenses. Ultrasonic irrigation enhances root canal cleaning, leading to improved endodontic success. Objective: The study aims to determine the knowledge, practice, and attitude of ultrasonics in endodontics among the general practitioners, endodontics postgraduates and endodontists of Nepal. Methods: A self-administered questionnaire containing questions regarding the knowledge, attitude, and practice of ultrasonics in endodontics was distributed to 151 general practitioners, postgraduates and endodontists working in Nepal. Data was collected and entered in Microsoft Excel sheet and analysis was done using Statistical Package of Social Sciences (SPSS) software version 16. Descriptive statistical analysis was done using mean, proportion and percentage. Results: Although 96% of dentists knew about ultrasonic endodontics, only 25% used it routinely. Common uses included; irrigation 65% and removing blockages 60%. Most of them (68.9%) preferred 3% or less sodium hypochlorite as passive activation of irrigation solution by ultrasonics. High equipment cost (71%) and heat generation (35%) were major usage barriers. Conclusion: In the present study, we found that the majority of the participants were well aware of the use of ultrasonics in endodontics and had adequate knowledge regarding the working principle and the type of ultrasonics used. But they don’t use it routinely in their practice.